Development of 28GHz and 77GHz 1MW gyrotron for ecrh of magnetically confined plasma - Kariya, T; Minami, R; Imai, T; Sakamoto, K; Kubo, S; Shimozuma, T; Takahashi, H; Ito, S; Mutoh, T; Mitsunaka, Y; Endo, Y; Shidara, H; et al. (2009)
We are developing a new 28GHz 1MW and a 77GHz 1MW gyrotron for ECRH system of tandem mirror GAMMA10 and Large Helical Device (LHD), respectively. The detail design study of 28GHz 1MW gyrotron such as cavity, magnetron injection gun (MIG) has been done. We obtained the oscillation power of 1.37MW and the oscillation efficiency of 42.7% with the pitch factor of 1.2. Two 77GHz 1 MW gyrotrons have been fabricated and tested. The maximum output power of 1.1 MW was obtained. The pulse width with 0.46MW extended to 5s with the short aging time of only 65 hours. A plasma injection for LHD with MOU output of 0.81MW 3.6s was performed.